Morphogenetic identification, description and pathogenicity of novel pathogens on Iraqi wheat plant (Triticum aestivum) causing head blight and crown rot diseases - MOHANAD KHALAF MOHAMMED-AMEEN; Mohammed Hussein Minati; Mohammed Abbas (Society for Indonesian Biodiversity, 2021)
Abstract. Mohammed-Ameen MK, Minati MH, Abbas MH. 2021. Morphogenetic identification, description and pathogenicity of novel pathogens on Iraqi Wheat Plant (Triticum aestivum) causing head blight and crown rot diseases. Biodiversitas 22: 2999-3005. Wheat (Triticum aestivum L.) plant suffers from several fungal diseases, such as Fusarium head blight, root rot, and crown rot diseases that reduce the quality and quantity of grains. Two Fusarium species (Fusarium brachygibbosum and F. falciforme) have been isolated from wheat roots and rhizosphere regions showing disease symptoms in wheat fields in Al-Hwuir and Al-Qurna districts at Basra province. Each fungal species had been characterized morphologically and molecularly based on DNA sequence data for the translation elongation factor 1- ? (TEF-1 ?). Results of pathogenicity test showed that F. falciforme and F. brachygibbosum at the third week of inoculation induced head bleached symptoms with the severity of 12.46% (with significant differences P > 0.05) and 7.14%, respectively on Abu Ghraib 3 cultivar. Yellowing and necrosis symptoms were recorded in stem and crown region. The mean of disease severity (as necrosis on basal stem and crown) was 5% and 3.34% for F. falciforme and F. brachygibbosum, respectively. The two Fusarium species were identified as new pathogens on wheat plants in Iraq, causing head bleaching, stem and crown necrosis.